Global Monitoring Report 2006 : Millennium Development Goals - Strengthening Mutual Accountability, Aid, Trade, and Governance - World Bank; International Monetary Fund (Washington, DC: World Bank, 2012)
One decade remains to meet the Millennium Development Goals (MDGs) that the international community set out in 2000. Yet the world is still far from achieving the MDGs. This Global Monitoring Report (GMR) reviews the efforts under way to strengthen mutual accountability. Greater resource flows to developing countries must go hand in hand with measures to make aid work more effectively. One key element is improving governance, both in developing countries and globally, to strengthen accountability for resource use and for development outcomes. Measuring and monitoring governance, in support of greater accountability and better MDG outcomes, is the primary focus of this report. Monitoring governance can help to clarify options for scaling up assistance and can support broader efforts to strengthen transparency and accountability, both nationally and globally. The report highlights six key actions to accelerate progress toward the MDGs and strengthen mutual accountability: Favorable growth has helped reduce poverty, but more even and accelerated progress requires strengthening of infrastructure and national investment climates. Recent progress in human development outcomes points to the need for more flexible aid, better coordination, and improved governance. Major aid and debt relief commitments were made in 2005, but vigilant monitoring is needed to guard against risks to their effective implementation. Trade reform needs new life. The focus of the international financial institutions (IFIs) must shift from managing inputs to achieving real results on the ground, but this poses major challenges to both the IFIs and developing countries. Governance should be regularly monitored to help track progress, generate greater accountability, and build demand for further progress. The international community must support efforts to strengthen governance systems through ratification and support for global checks and balances.